IDENTIFYING MILD COGNITIVE IMPAIRMENT AT BASELINE IN THE GINKGO EVALUATION OF MEMORY (GEM) STUDY - Snitz, Beth E. (2009)
OBJECTIVES: To identify, characterize and compare the frequency of Mild Cognitive Impairment (MCI) subtypes at baseline in a large, late-life cohort (N=3,063) recruited into a dementia prevention trial. METHOD: A retrospective, data-algorithmic approach was used to classify participants as cognitively normal or MCI with corresponding subtype (e.g., amnestic vs. non-amnestic, single domain vs. multiple domain) based on a comprehensive battery of neuropsychological test scores, with and without Clinical Dementia Rating (CDR) global score included in the algorithm. RESULTS: Overall, 15.7% of cases (n=480) were classified as MCI. Amnestic MCI was characterized as unilateral memory impairment (i.e., only verbal or only visual memory impaired) or bilateral memory impairment (i.e., both verbal and visual memory impaired). All forms of amnestic MCI were almost twice as frequent as non-amnestic MCI (10.0% vs. 5.7%). Removing the CDR = 0.5 (“questionable dementia”) criterion resulted in a near doubling of the overall MCI frequency to 28.1%. CONCLUSION: Combining CDR and cognitive test data to classify participants as MCI resulted in overall MCI and amnestic MCI frequencies consistent with other large community-based studies, most of which relied on the “gold standard” of individual case review and diagnostic consensus. The present data-driven approach may prove to be an effective alternative for use in future large-scale dementia prevention trials.